Visual Discomfort and the Temporal Properties of the Vergence-Accommodation Conflict - Kim, Joohwan; Kane, David; Banks, Martin S (Proceedings of SPIE, the international society for optical engineering, 2012)
The vergence-accommodation conflict associated with viewing stereoscopic 3D (S3D) content can cause visual discomfort. Previous studies of vergence and accommodation have shown that the coupling between the two responses is driven by a fast, phasic component. We investigated how the temporal properties of vergence-accommodation conflicts affect discomfort. Using a unique volumetric display, we manipulated the stimulus to vergence and the stimulus to accommodation independently. There were two experimental conditions: 1) natural viewing in which the stimulus to vergence was perfectly correlated with the stimulus to accommodation; and 2) conflict viewing in which the stimulus to vergence varied while the stimulus to accommodation remained constant (thereby mimicking S3D viewing). The stimulus to vergence (and accommodation in natural viewing) varied at one of three temporal frequencies in those conditions. The magnitude of the conflict was the same for all three frequencies. The young adult subjects reported more visual discomfort when vergence changes were faster, particularly in the conflict condition. Thus, the temporal properties of the vergence-accommodation conflict in S3D media affect visual discomfort. The results can help content creators minimize discomfort by making conflict changes sufficiently slow.